Esophageal metastasis of renal cancer 10 years after nephrectomy - Izumo, Wataru (Esophagus, 2014)
The patient was a 65-year-old man, who had undergone right nephrectomy for renal cancer in 2002. At that time, histopathological examination revealed clear cell carcinoma (pT3a, pN0, M0, and pStage III). Postoperatively, he received natural interferon alpha (6 million units 3 times a week) from November 2002 to February 2005, and showed no evidence of recurrence. However, he noticed dysphagia in March 2012. Endoscopy revealed a pedunculated polypoid tumor in the mid-esophagus and biopsies were taken showing a clear cell carcinoma. Contrast-enhanced thoracoabdominal CT scanning identified a pedunculated polypoid tumor in the mid-thoracic esophagus and enlargement of a lymph node adjacent to the right main bronchus. With a diagnosis of esophageal and lymph node metastases of renal cancer, the patient underwent esophagectomy with right thoracotomy with reconstruction by a posterior mediastinal stomach tube. Postoperative histopathological examination revealed clear cell carcinoma. Because esophageal metastasis of renal cancer is extremely rare, this case is reported here together with discussions of the relevant literature.